Exp AR Malacca: A Self-Guided Learning of Malacca’s Malay Traditional Houses using Augmented Reality Technology and Physical Map - Azhar, Siti Nur Farah Natasha; Saari, Erni Marlina; Hendriyani, Yeka; Shishah, Wesam (Journal of ICT in Education, 2025)
As a UNESCO World Heritage Site in Malaysia, Malacca is known for its traditions and historical treasures, notably traditional Malay houses. These houses are architectural jewels that represent the multiracialism and historical evolution of the Malay community, but major challenges such as urbanization, reduced accessibility, and a lack of public awareness make preserving them more challenging. Hence, this study employs the ADDIE model to develop the Exp AR: Malacca, an augmented reality (AR) application in an attempt to promote Malacca’s traditional Malay houses to tourists and to preserve its cultural and historical significance. The app bridges the gap between modern technology and heritage preservation by overlaying interactive 3D models of traditional Malay houses, historical insights, and immersive features. Through interviews and observations, the research incorporates feedback from two industry experts, two residents, and five tourists. The result shows a high rate of satisfaction regarding the users’ experience and engagement, with some recommendations for improvement. Using AR and a physical map as tools, this project proposes how technology could reshape cultural tourism by making tourism to heritage sites more engaging while fostering a deeper appreciation for Malacca’s legacy. The contribution of this research is to provide insights for sustainable tourism development and the adoption of digital technologies in cultural heritage management, ensuring traditional Malay houses in Malacca continue to be appreciated and preserved for future generations.